KINETICS AND MECHANISM OF GRAFT POLYMERIZATION OF ACRYLONITRILE ONTO STARCH INITIATED WITH POTASSIUM PERSULFATE (Journal of Sciences, Islamic Republic of Iran)
A new potassium persulfate redox system has been investigated for the graft polymerization of vinyl monomers. In this study potassium persulfate system was used for initiation the polymerization. Graft polymerization of acrylonitrile (AN) onto starch (Sta) was carried out in aqueous solution using potassium persulfate (I) redox system. It was found that the percentage of grafting and rate of grafting were all dependent to some extent, on the concentration of the I, AN, Sta and Sta/ water as well as reaction time and temperature. The kinetics of the graft polymerization of AN onto Sta in aqueous solution was studied by Kjeldahl method (quantity and qualitative determination nitrogen content), and the kinetics of AN homopolymerization in the same system was studied by bromometry titration (residue monomer determination). The following rate expression (rate of graft polymerization and rate of homopolymerization) Rg=k?[AN]1.185?[I]0.499?[Sta]0.497 and Rh=k?[AN]1.359?[I]0.436 were obtained and a suitable mechanism was suggested. The graft copolymer was investigated with an infrared spectroscope. The overall activation energy was found to be 56.95 kJ/mol within the temperature range of 40-65°C.